2004
DOI: 10.1021/ol049331x
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Cochleamycin A

Abstract: [reaction: see text] Cochleamycin A (1) was synthesized in 2.4% overall yield via a 23-step linear sequence starting from 3-butene-1-ol. Key features of the synthesis include the synthesis of (Z)-1,3-diene 21 via a Stille coupling of 4 and 5 and a transannular Diels-Alder reaction of macrocycle 26 to provide the complete carbon skeleton of 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 29 publications
0
31
0
1
Order By: Relevance
“…23 In our study, mild reducing agents like di-isobutyl aluminium hydride [DIBAL (1M in Toluene)] was used to reduce picene-13-carboxylic acid ethyl ester 6 to picen-13-ylmethanol 9 24 in 90% yield. It was found that the oxidation of compound 9 with manganese dioxide 11 in dichloromethane was not completed even under reflux condition.…”
Section: Resultsmentioning
confidence: 99%
“…23 In our study, mild reducing agents like di-isobutyl aluminium hydride [DIBAL (1M in Toluene)] was used to reduce picene-13-carboxylic acid ethyl ester 6 to picen-13-ylmethanol 9 24 in 90% yield. It was found that the oxidation of compound 9 with manganese dioxide 11 in dichloromethane was not completed even under reflux condition.…”
Section: Resultsmentioning
confidence: 99%
“…The crude aldehyde was then directly transformed into the ( Z) -α,β-unsaturated ester 62 as a single stereoisomer by a Still–Gennari [72] olefination with phosphonate 61 in an excellent yield of 93% over 4 steps. After reduction of ester 62 to the corresponding aldehyde (by a method that was not specified by the authors) phosphorane 63 was used to generate the respective Z -vinyl iodide in 85% yield as an 8:1 ( Z , Z) :( Z , E) mixture [91] which was later switched to the stannane 56 by lithium–halogen exchange and further treatment with Bu 3 SnCl [92] in 90% yield.…”
Section: Reviewmentioning
confidence: 99%
“…Not surprisingly, the combination of architectural complexities and bioactivities has engendered considerable interest, resulting in impressive synthetic studies from the groups of Paquette and Tadano using Diels-Alder reactions [107][108][109][110]. After our first total synthesis of cochleamycin A [97], Tadano's group reported the total synthesis of macquarimicin A (100) [109,110], and Roush's group disclosed his total synthesis of cochleamycin A [111]. Both groups took transannular Diels-Alder reactions to construct cochleamycin skeleton, as the formation of a 10-membered ring had been well known to be difficult.…”
Section: The Total Synthesis Of Cochleamycin Amentioning
confidence: 99%